Reproduction in the Annelida - Hill, Susan D.; Saglam, Naim; Shain, Daniel H. (Elsevier, 2018)
The Phylum Annelida - segmented worms - comprises the polychaetes (marine worms) and the clitellates (oligochaetes including leeches), as well as some recently added taxa (Echiuroidea, Sipuncula, Siboglinidae). As a group, annelids are found abundantly in oceanic, freshwater and terrestrial environments, and display a variety of reproductive behaviors ranging from fertilization in the open water to asexual fragmentation. Many marine worms reproduce sexually with independent sexes and pass through a motile trochophore larvae stage, while clitellates are hermaphrodites (containing both male and female gonads) with a specialized reproductive structure, the clitellum, which secretes a protective cocoon for embryo development. Exceptions to these common reproductive modes occur, and have facilitated the widespread distribution of annelids throughout the biosphere. © 2018 Elsevier Inc. All rights reserved.
Keywords: Chaetae; Clitellata; Clitellum; Egg capsule; Hermaphrodite; Hirudinid; Leech; Oligochaete; Operculum; Polychaete; Setae; Spermatophore; Trochophore; Worm